2020
DOI: 10.3390/nano10071418
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity to RAW264.7 Macrophages of Silica Nanoparticles and the E551 Food Additive, in Combination with Genotoxic Agents

Abstract: Synthetic amorphous silica (SAS) is used in a plethora of applications and included in many daily products to which humans are exposed via inhalation, ingestion, or skin contact. This poses the question of their potential toxicity, particularly towards macrophages, which show specific sensitivity to this material. SAS represents an ideal candidate for the adsorption of environmental contaminants due to its large surface area and could consequently modulate their toxicity. In this study, we assessed the toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…In the present work, the cytotoxicity of UCNP cores coated with silica shells was investigated in the macrophage cell line RAW 264.7. RAW 264.7 cells are particularly sensitive to the treatment with nanoparticles [42][43][44]. They are an established model of activated macrophages and they actively take up nanomaterials from biological media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, the cytotoxicity of UCNP cores coated with silica shells was investigated in the macrophage cell line RAW 264.7. RAW 264.7 cells are particularly sensitive to the treatment with nanoparticles [42][43][44]. They are an established model of activated macrophages and they actively take up nanomaterials from biological media.…”
Section: Introductionmentioning
confidence: 99%
“…This way, RAW264.7 cells mimic the behavior of macrophages and other immune cells, which eliminate foreign substances from the organism. Moreover, they have already been applied in studies involving uncoated NaGdF 4 [42] and silica particles [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous Si-NPs have striking characteristics for application as drug carriers because they can adsorb and release drug molecules. However, Si-NPs can absorb toxic agents on the cell surface, increasing their toxicity potential [ 18 ].…”
Section: Characteristics Of Nmsmentioning
confidence: 99%
“…However, as ultrafine particle and nanoparticle physicochemical features may overlap, it has been suggested that their behaviors and toxicities may also overlap (Stone et al, 2017). In addition, beside inhalation, nanoparticles can also enter the body through oral exposure and co-ingestion of nanoparticles and other pollutants such as pesticides for instance may also induce adverse effects on human health, especially on the gastro-intestinal tract (Cao et al, 2021(Cao et al, , 2019Dussert et al, 2020;Shi et al, 2010;Zheng et al, 2012). Moreover, nanoparticles incorporated in consumer products can be freed during the life cycle of the products, from their manufacture to their end-of-life.…”
Section: Air Pollutionmentioning
confidence: 99%
“…This explains why some studies investigated the damages to the cardio-vascular system (Asweto et al, 2017;Feng et al, 2018Feng et al, , 2017 and to other organs (Cotena et al, 2021;Courter et al, 2007;Deville et al, 2016;Ku et al, 2017;Lai et al, 2020;Roje et al, 2019;Schirinzi et al, 2017;Teng et al, 2020;Xia et al, 2011). Among the different organs, the digestive system is quite well studied (Ahamed et al, 2020a(Ahamed et al, , 2019bCao et al, 2021Cao et al, , 2019Dussert et al, 2020;Shi et al, 2010;Zheng et al, 2012). Indeed, inhaled nanoparticles can reach this system after translocation or due to swallowing after mucocilliary clearance of particles from the airways.…”
Section: A Literature Review On the Joint Toxicity Of Nanoparticles And Co-contaminantsmentioning
confidence: 99%